The Relationship between Iron Intake and Anemia in Elementary School Children in the Working Area of the Air Beliti Public Health Center, Musi Rawas Regency - Meliyanti Meliyanti; Rostika Flora; Najmah Najmah (Budapest International Research and Critics University, 2021)
Anemia is a health problem that often occurs in school-age children. Low iron intake is the most common cause of anemia in children. Anemia has an impact on physical growth disorders and decreased body resistance. The purpose of this study was to analyze the relationship between iron intake and the incidence of anemia in schoolchildren. This research is an analytic observational study with a cross-sectional design. The Hb examination was carried out to find out the anemia while the iron intake data was assessed by observation on a 24-hour dietary recall. The sample in this study was 80 elementary school children, with a simple random sampling method at five schools in the working area of Air Beliti Public Health Center. The HB examination result showed that 51.2% of respondents had anemia, while the dietary recall showed that 26.2% of children had insufficient iron intake. The statistical test showed that 81.0% of children with insufficient iron intake suffered from anemia. There was a significant relationship between iron intake and the incidence of anemia in elementary school-aged children in the working area of Air Beliti Public Health Center, Musi Rawas Regency (p=0,004; OR=6.198). Based on the results of the study, it can be concluded that there is a significant relationship between iron intake and the incidence of anemia in schoolchildren. Children with low iron intake are 6.198 times more likely to suffer from anemia. Therefore, it is recommended for parents to maintain a balanced nutritional and iron-rich food intake to prevent the incidence of anemia in children. As for the public health center to improve health education and socialization for parents regarding balanced nutrition and foods containing iron for schoolchildren.